The influence of watering practices on the transmission of Fasciola among sheep in the Ethiopian highlands - Njau, B.C.; Kasali, O.B.; Scholtens, R.G.; Akalework, N. (Springer, 1989)
A study conducted to evaluate transmission rates of fascioliasis, using parasite-free ewes and their lambs as tracer animals, under dif. watering practice and to assess the value of enzyme-linked immunosorbent assay (ELISA) in studying the epidemiology of the disease.